2014
DOI: 10.1200/jco.2013.54.4601
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer After Chest Radiation Therapy for Childhood Cancer

Abstract: Among women treated for childhood cancer with chest radiation therapy, those treated with whole-lung irradiation have a greater risk of breast cancer than previously recognized, demonstrating the importance of radiation volume. Importantly, mortality associated with breast cancer after childhood cancer is substantial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
183
1
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 255 publications
(200 citation statements)
references
References 27 publications
8
183
1
8
Order By: Relevance
“…Epidemiological studies have been carried out in several countries for investigation of cancer risk among medical radiation workers, such as radiologists studied in the UK (Doll, 2005) and the U.S (Matanoski et al, 2008), radiological technologists studied in the U.S (Little et al, 2014;Moskowitz et al, 2014) and Japan (Yoshinaga et al, 1999), and radiotherapy staff studied in Denmark (Andersson et al, 1991). Breast cancer is believed to be one of the most readily caused by ionizing radiation (Snijders et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have been carried out in several countries for investigation of cancer risk among medical radiation workers, such as radiologists studied in the UK (Doll, 2005) and the U.S (Matanoski et al, 2008), radiological technologists studied in the U.S (Little et al, 2014;Moskowitz et al, 2014) and Japan (Yoshinaga et al, 1999), and radiotherapy staff studied in Denmark (Andersson et al, 1991). Breast cancer is believed to be one of the most readily caused by ionizing radiation (Snijders et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…9,12,24 Thirty years after treatment, at attained ages of #51 years, the cumulative incidence of breast cancer in survivors treated before age 21 was as high as 26%, 25,28 which is comparable to the risk of breast cancer gene mutation carriers. 26,29 For lung cancer, SIRs do not decrease with increasing age at HL treatment as strongly as for breast and gastrointestinal tract cancers; the SIR was still 5.2-fold increased for patients treated at ages 35 to 51 years. 24 Also, increased SIRs for lung cancer appears to become manifest earlier (5 to 9 years from first treatment) than for breast and gastrointestinal tract cancers.…”
Section: Introductionmentioning
confidence: 96%
“…13 For patients treated at age 25 years with a chest radiation dose of at least 40 Gy without alkylating agents, the estimated cumulative absolute risks of breast cancer by age 35, 45, and 55 years were 1.4%, 11.1%, and 29.0%, respectively. Several studies have demonstrated a direct correlation between breast cancer risk and radiation field size [14][15][16][17] and also showed that smaller fields and treatment volume are associated with a significantly lower risk of breast cancer. In a population-based study comparing outcome of de novo breast cancer versus breast cancer after HL, women with localized breast cancer after HL had a significantly increased 2-fold risk of death from breast cancer compared with patients with de novo breast cancer.…”
Section: Second Malignancymentioning
confidence: 99%